Problematika Penerapan Mudharabah Mutlaqah di BMT UGT Nusantara Capem Blega Bangkalan - Edi Lukman Hakim (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2023)
Â AbstractBMT Nusantara Blega Bangkalan Branch is one of the Islamic financial institutions that runs its business with a profit-sharing system without usury. One of the products is mudharabah mutlaqah financing. The fact shows that public interest in mudharabah mutlaqah financing is still very minimal. This research uses a qualitative approach with a case study approach. The research results are known. First, Mudharabah mutlaqah BMT Nusantara Financing for the Blega Bangkalan Branch did not run smoothly, this was caused by a lack of understanding of entrepreneurs in Blega village regarding the BMT mechanism and its products, to overcome this problem BMT UGT Nusantara implemented a solution in the form of understanding for entrepreneurs who did not understand the mudharabah financing mechanism mutlaqah, this aims to eliminate the negative stigma of entrepreneurs in Blega village related to this financing. The settlement of mudharabah mutlaqah financing problems is also accompanied by risk management by BMT UGT Nusantara, this aims to prevent similar problems in the futureKeywords: Problematics, Mudharabah Mutlaqah Financing, BMT UGT